Assessment of Parental Needs and Quality of Life in Children with a Rare Neuromuscular Disease (Pompe Disease): A Quantitative–Qualitative Study - Loredana Benedetto; Olimpia Musumeci; Annunziata Giordano; Mattia Porcino; Massimo Ingrassia (Behavioral Sciences, 2023)
Pompe disease (PD) is a rare metabolic disorder with progressive neuromuscular consequences that negatively impact a child’s development and quality of life (QoL). Despite an improved prognosis with treatment, the risk for early death due cardiorespiratory crisis remains. Parents not only face physical fatigue and family distress in coping with the child’s special needs but also experience emotions, worries, and unexpressed needs (a “humanistic burden”) that require supportive interventions. Fourteen parents of children with PD completed an online self-report questionnaire assessing their child’s QoL, their own parental burden of care, and disease-related issues. The aim was to estimate the associations between the child’s QoL and the caregiver’s burden levels. Three mothers were also interviewed. A total of 57.1% of parents lived with moderate/severe burden conditions; worse QoL for the child was associated with higher levels of caregiver burden (rS[N = 14] = −0.67, p < 0.01). Uncertainty about the child’s future was a state commonly described by mothers. However, the child’s resilience, normalization of disease, and coping strategies (primarily positive appraisal and focusing on the present) alleviated suffering and helped mothers maintain family functioning. Finally, dissatisfaction with communication in relationships with professionals emerged. In conclusion, a typical pediatric palliative care approach is recommended since it manages to guarantee parents empathetic and supportive communication from healthcare professionals, alleviating feelings of isolation and loneliness in parents.